Analysis of Bitcoin Volatility during the COVID-19 Pandemic: An Examination Using ARCH and GARCH Models - Vildan Bayram; Ulaş Ünlü (Ekonomi, Politika & Finans Araştırmaları Dergisi)
The COVID-19 pandemic has had a profound effect on the global economy and financial markets, including a significant impact on the cryptocurrency markets. This study analyzes the impact of the COVID-19 process on bitcoin price movements. The study examines the daily price data of bitcoin between 01/03/2020 and 01/04/2022 and uses ARCH and GARCH models to estimate volatility. The results show that there was a significant increase in bitcoin volatility during the initial period of the pandemic. This reflects a period when the pandemic increased uncertainty in financial markets and spurred investor interest in cryptocurrencies. While the ARCH model showed limited success in analyzing the short-term dynamics of volatility, the GARCH model captured the long-term trends in volatility more effectively. However, both models were insufficient to fully predict the sudden and extreme increases in volatility observed during crisis periods such as the pandemic. In addition to analyzing the impact of the pandemic on cryptocurrency markets, the study provides important implications for investor behavior and volatility management. In this context, it highlights the importance of developing risk management and regulatory frameworks in cryptocurrency markets.